Hydrolysis of Palm Kernel Cake (Elaeis guineensis Jacq) by Fungi Trichoderma reesei that Degrades Mannan Polysaccharides - Jaelani, A; Piliang, WG; Suryahadi, Suryahadi; Rahayu, I (ANIMAL PRODUCTION, 2008)
The research was conducted to study the growth characterization of Trichoderma reesei, the degradability of mannan polysaccharides from Palm Kernel Cake (PKC) with different concentrations of fungi and thickness of the PKC medium, as well as the improvement of the nutritive value of palm kernel cake. Experiment 1 was to study the growth characterization of Trichoderma reesei, and Experiment 2 was conducted using concentrations of fungi (104, 105, and 106 CFU per cc) and thickness of the PKC medium (1, 2, and 3 cm). The research used a completely randomized design with factorial 3 x 3. The treatments resulted in significant (P<0.05) differences on pH and temperature of PKC medium, ADF, NDF, crude protein, and hemicellulose.Â  There were interaction effect on the concentrations of fungi and on the thickness of PKC medium (P<0.05) on NDF, crude protein, and hemicelluloses (P<0.05). Experiment 3 was conducted to study the True Metabolizable Energy (TME), the retention of nitrogen, total sugar and mannan content. Results showed that Trichoderma reesei was able to degrade mannan polysaccharides of PKC whereby TME and the total sugar value increased, but the nitrogen retention and mannan content decreased. (Animal Production 10(1): 42-49 (2008)Â Key Words: Hydrolysis, palm kernel cake, Trichoderma reesei, mannan polysaccharides